Interventions to reduce prejudice and enhance inclusion and respect for ethnic differences in early childhood: a systematic review - Aboud, Frances E.; Tredoux, Colin; Tropp, Linda R.; Brown, Christia Spears; Niens, Ulrike; Noor, Noraini M. (Elsevier, 2012)
A systematic review was conducted of studies evaluating the effects of interventions aimed at reducing ethnic prejudice and discrimination in young children. Articles published between 1980 and 2010 and including children of 8 years and under were identified, harvested, and assessed for quality, both for the exposure/program as well as for the evaluation. In total, 32 studies (14 contact and 18 media or instruction) yielded 62 effects on attitudes and 59 effects on peer relations. An overall count of the positive (40%), non-significant (50%), and negative effects (10%) indicate a mixed picture. Overall, more attitude effects (55%) than peer relations effects (25%) were positive, and media/instruction (47%) was more successful than contact (36%). Most of the effects were observed with children from a majority ethnicity: 67% of the attitude effects were positive, and media/instruction and contact were equally effective at delivering these. Few differences were found as a function of the quality of the exposure and evaluation, but differences were found depending on the context of exposure (naturally occurring or experimental manipulation) and research design (random assignment or self-selection). In conclusion, the findings were more mixed than expected, though sufficiently strong studies exist to provide lessons for future research.